The obstacles of educational supervision facing educational supervisors in the directorates of education in the south of the Hashemite Kingdom of Jordan from their point of view - Ghoneim, Sahar Thiab Salman (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to uncover the administrative and technical supervisory constraints of the educational supervisors in the directorates of education in southern Jordan from their point of view. To achieve the objectives of the study, the researcher used the descriptive method. The questionnaire was distributed to a sample of (75) supervisors, representing (%77) of the study population, and using the statistical program (spss). A total average of (4.16), and at the level of the two axes; the axis of administrative obstacles got an average of( 4.24) followed by the axis of physical obstacles, with an average (4.09) and all (high), and the results showed that there are no statistically significant differences between Educational supervisors looked at physical and administrative constraints, and in the light of the results were presented The religion of recommendations and proposals to overcome the obstacles facing the supervisors’ directorates of education in the south, and all directorates of the Kingdom.